2013
DOI: 10.1186/1756-6606-6-12
|View full text |Cite
|
Sign up to set email alerts
|

Synaptosomal-associated protein 25 mutation induces immaturity of the dentate granule cells of adult mice

Abstract: BackgroundSynaptosomal-associated protein, 25 kDa (SNAP-25) regulates the exocytosis of neurotransmitters. Growing evidence suggests that SNAP-25 is involved in neuropsychiatric disorders, such as schizophrenia, attention-deficit/hyperactivity disorder, and epilepsy. Recently, increases in anxiety-related behaviors and epilepsy have been observed in SNAP-25 knock-in (KI) mice, which have a single amino acid substitution of Ala for Ser187. However, the molecular and cellular mechanisms underlying the abnormalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
62
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 83 publications
5
62
0
Order By: Relevance
“…Similar changes in DG neurons have been demonstrated in αCaMKII HKO [11], Shn-2 KO [18], and SNAP-25 KI mice [19]; this phenomenon has been termed the “immature DG” [10]. In this study, we demonstrate for the first time that FLX treatment might also induce dematuration of parvalbumin+ interneurons in the mFC and hippocampal CA3 region, while our finding in the amygdala is consistent with that of a previous study [20].…”
Section: Discussionsupporting
confidence: 73%
“…Similar changes in DG neurons have been demonstrated in αCaMKII HKO [11], Shn-2 KO [18], and SNAP-25 KI mice [19]; this phenomenon has been termed the “immature DG” [10]. In this study, we demonstrate for the first time that FLX treatment might also induce dematuration of parvalbumin+ interneurons in the mFC and hippocampal CA3 region, while our finding in the amygdala is consistent with that of a previous study [20].…”
Section: Discussionsupporting
confidence: 73%
“…To date, we have detected brain immaturity in various situations and hypothesized that the hyper-excitability of neurons is one of the causes of pseudo-immaturity in the hippocampus and PFC4; other reports also support an association between the hyper-excitation of neurons and neuronal dematuration910. In the present study, we detected immaturities in the brains of patients with alcoholism.…”
Section: Discussionsupporting
confidence: 67%
“…Commentaries in response to the previous study claim that the implications of the study by Seok et al (1) may well go beyond mice and sepsis (10), and that better definitions of clinical phenotypes, especially in heterogeneous or overlapping conditions such as neurodevelopmental and psychiatric diseases, as well as more emphasis on rigorously defining molecular alterations in human patients, is needed (8). It should be noted that, even for schizophrenia, which could be considered a uniquely human disorder (17), recent mouse models have been developed using an approach similar to those used in the present study that are shown to closely recapitulate not only the clinical or behavioral phenotypes but also the molecular alterations in transcriptional and protein changes in the brain (18)(19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%